Redes de valor verdes - Avelino, Juscimara Gomes (2019)
Value networks represent an array of actors, activities, and commercial value objects configured to meet the needs of a market segment. The main goal is to set it up for business networks that are potentially sustainable. However, a sustainability approach addressed by the e3value is purely economic, and this is not a single perspective. Sustainability has an important perspective, which is its sustainability. The importance of this dimension, this research is an indicator of an ontology of networks of green values. The significant point of a green value network is a business need, it is no longer able to be satisfied by the core business object, complemented by an object of proof, which indicates its environmental origin. The tests are indispensable, the ones that concern are certified environmental. Thus, there were five organizational standards that have an arrangement of certifications and tests, which are granted and aggregated by the actors of the network. For purposes of validation, the method of searching for technical actions was used in a local case study in a company in the agribusiness sector. With the research of technical action, it was possible to investigate the process of searching for environmental certifications and to extinguish the validation of the ontology and the organizational standards